2021
DOI: 10.3389/fphys.2021.707724
|View full text |Cite
|
Sign up to set email alerts
|

Microvolt T-Wave Alternans Is Modulated by Acute Low-Level Tragus Stimulation in Patients With Ischemic Cardiomyopathy and Heart Failure

Abstract: Aims: Microvolt T-wave alternans (TWA), an oscillation in T-wave morphology of the electrocardiogram (ECG), has been associated with increased susceptibility to ventricular tachy-arrhythmias, while vagus nerve stimulation has shown promising anti-arrhythmic effects in in vivo and ex vivo animal studies. We aimed to examine the effect of non-invasive, acute low-level tragus stimulation (LLTS) on TWA in patients with ischemic cardiomyopathy and heart failure.Methods: 26 patients with ischemic cardiomyopathy (lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Existing data show the beneficial effect of VNS in reducing inflammatory markers, and this may be the primary mechanism for improving clinical outcomes across many cardiovascular diseases. However, more studies are needed to elucidate the mechanisms linking the improvement of the inflammatory state following VNS with clinical outcomes in patients with heart failure, 59 myocardial ischemia, 59 and arrhythmias. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data show the beneficial effect of VNS in reducing inflammatory markers, and this may be the primary mechanism for improving clinical outcomes across many cardiovascular diseases. However, more studies are needed to elucidate the mechanisms linking the improvement of the inflammatory state following VNS with clinical outcomes in patients with heart failure, 59 myocardial ischemia, 59 and arrhythmias. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are needed to elucidate the mechanisms linking the improvement of the inflammatory state following VNS with clinical outcomes in patients with heart failure, 59 myocardial ischemia, 59 and arrhythmias. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have also demonstrated the potential of cardiac alternans as a biomarker of vagal stimulation treatment efficacy in patients with both atrial and ventricular tachyarrhythmias [ 12 , 49 ]. Cardiac alternans was shown to be modulated by both acute and chronic changes in electrophysiological substrate by vagus nerve stimulation.…”
Section: Future Scope: Can Atrial Alternans Guide Atrial Fibrillation...mentioning
confidence: 99%
“…Even though treatment of cardiac arrhythmias through automatic modulation has proven results preclinically, large randomized clinical trials have shown mixed results ( Premchand et al, 2014 ; Zannad et al, 2015 ; Gold et al, 2016 ; Stavrakis et al, 2020b ), highlighting the need for optimized biomarkers enabling appropriate patient selection. Yet, recent studies have demonstrated that vagal stimulation can modulate cardiac electrophysiological properties ( Kulkarni et al, 2018b ; Lee et al, 2018 ) including both atrial and ventricular alternans ( Kulkarni et al, 2021b , c ) as well as reduce AF burden ( Qin and Singh, 2020 ; Stavrakis et al, 2020b ).…”
Section: Management Of Atrial Arrhythmiasmentioning
confidence: 99%